(untitled) (Vietnam Journal of Community Medicine, 2026)
Scleritis is a rare inflammatory ocular disease characterized by intense inflammation and severe ocular pain. The condition is highly destructive to ocular tissues; without timely diagnosis and intervention, it can lead to devastating complications, including permanent vision loss. We report two clinical cases of necrotizing fungal scleritis following pterygium surgery, with diagnoses confirmed through microbiological testing. Both patients presented with severe pain occurring between ten days and fourteen days post-operatively, showing no response to initial treatment with antibiotics and corticosteroids. The scleritis lesions originated at the surgical site and expanded circumferentially along the anterior sclera. Both patients were successfully managed using a multimodal treatment approach, comprising surgical debridement of necrotic scleral and conjunctival tissues (leaving the sclera bare) combined with intensive topical and systemic antifungal therapy.